2014
DOI: 10.1245/s10434-014-3583-z
|View full text |Cite
|
Sign up to set email alerts
|

Postgastrectomy Syndrome Assessment Scale (PGSAS)-45 and Changes in Body Weight are Useful Tools for Evaluation of Reconstruction Methods Following Distal Gastrectomy

Abstract: Although weight loss was significantly lower following BI procedures, esophageal reflux symptoms were significantly higher. Either BI or RY procedures may be recommended based on the individual patient's condition after distal gastrectomy. The newly developed QOL questionnaire, PGSAS-45 and changes in body weight proved useful for evaluation of QOL following gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 17 publications
4
39
3
Order By: Relevance
“…“Change in body weight” is often used as an index which objectively evaluates the physical status of postgastrectomy patients[21,22,27,28], but in this study, the influence of “change in body weight” per se on the postoperative QOL of gastrectomy patients was unexpectedly small.…”
Section: Discussionmentioning
confidence: 69%
“…“Change in body weight” is often used as an index which objectively evaluates the physical status of postgastrectomy patients[21,22,27,28], but in this study, the influence of “change in body weight” per se on the postoperative QOL of gastrectomy patients was unexpectedly small.…”
Section: Discussionmentioning
confidence: 69%
“…This comparison was performed using the PGSAS-45, a questionnaire developed to measure QOL in postgastrectomy patients. In the series of our cross-sectional study, we found that there was a little difference in the effect after DG between Billroth-I and Roux-en-Y procedure[10]. On the other hand, several clinical factors such as symptom severity, ability for working, and necessity for additional meals had a significant impact on postoperative QOL, while the influence of the extent of gastrectomy was unexpectedly small[6].…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical setting, excess body weight loss is not always accompanied with worse QOL, therefore, precise features of the impact of body weight loss on the postoperative QOL should be investigated. For this purpose, we studied the impact of body weight loss as well as postoperative BMI on the postgastrectomy QOL using the PGSAS-45 questionnaire, which is the first questionnaire developed to specifically measure QOL in gastrectomized patients[11,35-38], by multiple regression analysis. The results of our study demonstrated that the preoperative BMI rather than the degree of body weight loss was the most influential predictor of worse QOL after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%